The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.3989/redc.2015.4.1263
|View full text |Cite
|
Sign up to set email alerts
|

La relación entre las empresas españolas y el CSIC: motivaciones, mecanismos y beneficios desde la perspectiva empresaria

Abstract: Cómo citar este artículo/Citation: Valmaseda-Andia, O.; Albizu-Gallastegi, E.; Fernández-Esquinas, M.; Fernández-de-Lucio, I. (2015). La relación entre las empresas españolas y el CSIC: motivaciones, mecanismos y beneficios desde la perspectiva empresarial. Revista Española de Documentación Científica, 38(4): e109. doi: http://dx.doi.org/10.3989/redc.2015.4.1263Resumen: El presente trabajo explora las motivaciones por las que las empresas españolas interaccionan con el Consejo Superior de Investigaciones Cien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 31 publications
0
3
0
5
Order By: Relevance
“…Conversely, Toedtling et al (2012) study the Austrian information and communication technology sector and argue that, in global knowledge networks, local and regional relationships still matter for innovation. Other authors like Valmaseda-Andia et al (2015) have found that benefits obtained by companies through interaction with public research organizations.…”
Section: External Knowledge Sourcing As An Innovation Strategymentioning
confidence: 99%
“…Conversely, Toedtling et al (2012) study the Austrian information and communication technology sector and argue that, in global knowledge networks, local and regional relationships still matter for innovation. Other authors like Valmaseda-Andia et al (2015) have found that benefits obtained by companies through interaction with public research organizations.…”
Section: External Knowledge Sourcing As An Innovation Strategymentioning
confidence: 99%
“…Based on Valmaseda-Andia et al (2015). The first category is classified into operational, tactical and strategic motivations, as the common timing and scope of firms for planning and making decisions considered in management studies, as in Bilgen & Ozkarahan (2004).…”
Section: Othersmentioning
confidence: 99%
“…En la primera fase del trabajo de campo se realizó una encuesta a todas las empresas participantes utilizando como referencia el cuestionario estructurado de Valmaseda-Andia et al (2015). Los resultados obtenidos, tratados en un proceso informático y estadístico que permite cuantificar y segmentar opiniones y variables sociodemográficas y de otra índole, permiten conocer, evaluar y cuantificar los objetivos perseguidos.…”
Section: Metodologíaunclassified
“…Sobre él intervienen tanto las barreras derivadas de las culturas diferentes (Siegel et al, 2003) como dificultades generadas por los procesos burocráticos (Tartari et al, 2012). Si bien estas barreras son significativas en cualquier sistema de innovación, en las regiones periféricas con baja densidad industrial estas implican mayores dificultades para la innovación (Fernández-Esquinas, 2015). La mayor parte de estas barreras se incrementan a medida que disminuyen la estructura de oportunidad, las capacidades desarrolladas por los agentes y los recursos de los que se disponen para favorecer la transferencia.…”
Section: Introductionunclassified